Software para consulta de enfermagem aos hipertensos da Estratégia Saúde na Família. - dos Santos Santana, Jancelice; Lima da Nóbrega, Maria Miriam; dos Santos Oliveira, Jacira; Guimarães Oliveira Soares, Maria Júlia (Revista Brasileira de Enfermagem)
Objective: To report the development of a nursing consultation software for hypertensive users of the Family Health Strategy. Method: Applied methodological research based on Roger Pressman's Software Engineering, developed in three cycles: planning, composed of the definition of the database prototyping and modelling; development of the navigation interface; and development of functional expressions and programming. Result: The software consists of administrative and nursing consultation screens. In the history, there is the option of undertaking the first and next consultation; nursing diagnoses are suggested by the system after entering information and can be selected by nurses. Interventions for diagnoses are suggested and can be chosen by nurses after structuring the medical plan. Conclusion: It is believed that the introduction of computer technology for nursing consultation brings several contributions, such as standardization, integration with different information systems, and continuous update.